Space-time analysis of urban green areas in the Monterrey Metropolitan Zone, Mexico - Manzanilla-Quiñones, Ulises; Manzanilla-Quijada, Gyorgy Eduardo; Delgado-Valerio, Patricia (Ecosistemas y Recursos Agropecuarios, 2021)
Urban green areas (UGA) provide relevant ecosystem services to cities, unfortunately, they are vulnerable to urbanization processes. The objective of this study was to analyze under a spatio-temporal approach the UGA of the Metropolitan Zone of Monterrey (MZM). Landsat and Global Forest Change satellite images were used to estimate the UGA and environmental quality of the MZM for the period 2000-2019. A trend (p < 0.01) of UGA reduction was found from 2001 to 2019. The estimated environmental quality decreased from 13.21 (2000) to 7.75 m2 (2019). The UGA area was lost at a rate of 0.29 m2 per inhabitant per year. The municipalities of Juarez, Monterrey, Apodaca and Guadalupe were the ones that lost UGA. The conservation and protection of UGA should be priority activities for the civil authorities of the municipalities of the MZM, specifically, in the municipality of Juarez.